Luminescence properties and its red shift of blue-emitting phosphor Na3YSi3O9:Ce3+ for UV LED. Issue 44 (23rd May 2017) - Wang, Fei; Wang, Wanrong; Zhang, Liangliang; Zheng, Jinju; Jin, Ye; Zhang, Jiahua
Abstract : A series of Na3 YSi3 O9 :Ce 3+ phosphors have been synthesized via a conventional high temperature solid-state reaction. The emission red shift has been observed and explained by combining the centroid shift and crystal field splitting. Abstract : A series of Na3 YSi3 O9 :Ce 3+ phosphors have been synthesized via a conventional high temperature solid-state reaction. Each crystal structure was characterized by X-ray diffraction (XRD) and refined by the Rietveld method. Luminescence properties of Na3 YSi3 O9 :Ce 3+ phosphors such as emission red shifts, fluorescence decay curves, thermal stability, and CIE values were systematically investigated. Upon 300 nm excitation, the emission peaks of Na3 YSi3 O9 :Ce 3+ phosphors red shift from 385 nm to 415 nm with Ce 3+ concentration increasing from 0.002 to 0.11. Moreover, this red-shift phenomenon also occurs with an excitation wavelength from 270 nm to 340 nm as the Ce 3+ concentration determined, which has been explained using the centroid shift and crystal field splitting. The quenching concentration of Ce 3+ in the host Na3 YSi3 O9 is determined to be about 3 mol% and the critical distance is calculated to be about 16.623 Å. The energy dispersion mechanism between Ce 3+ ions was verified to be a dipole–dipole interaction. Temperature-dependent luminescence of Na3 YSi3 O9 :0.03Ce 3+ from 25 °C to 250 °C was evaluated, and the corresponding activation energy Δ E is 0.277 eV. Not only crystal field splitting but also centroid shift plays an important role in the red-shift of the Na3 YSi3 O9 :Ce 3+ phosphors, which may contribute to future research in designing novel solid phosphors by modifying composition of the host lattice to affect crystal field splitting and centroid shift, and then adjusting emission wavelengths to match the purposed application.